Fermentation of Oil Palm Trunk Acid Hydrolysate to Ethanol - H. H. Yeoh; K. O. Lim; M. D. Mashitah (ASEAN Journal on Science and Technology for Development, 2001)
Studies on the feasibility of using oil palm trunk acid hyd10lysates as a substrate for ethanol p10duction using the yeast Saccha10myces cerevisiae were carried out in shake flask culture. The effect of pH and fermentation time on the rate of ethanol p10duction were investigated. Results showed that with 3 hours fermentation period, the highest ethanol yield was obtained at pH 4.75. This yield was about 14% of the dry weight of the sample used; thus giving a fermentation efficiency of 94.7%.